Physiological and biochemical responses of Suaeda fruticosa to cadmium and copper stresses: growth, nutrient uptake, antioxidant enzymes, phytochelatin, and glutathione levels - Bankaji, I. (2020)
Environmental pollution by trace metal elements (TMEs) is a serious problem worldwide, increasing in parallel with the development of human technology. The present research aimed to examine the response of halophytic species Suaeda fruticosa to oxidative stress posed by combined abiotic stresses. Plants have been grown for 1 month with an irrigation solution supplemented with 200 mM NaCl and 400 μM Cd2+ or 400 μM Cu2+. The level of glutathione (GSH), phytochelatins (PCs), and antioxidant enzyme activities [ascorbate peroxidase (APX), guaiacol peroxidase (GPX), and catalase (CAT)] as well as lipid peroxidation was studied to see the stress exerted by the TME and the level of tolerance and detoxification strategy adopted by S. fruticosa. Relative growth rate (RGR) decreased under Cd2+ stress in this species, whereas Cu2+ did not have any impact on S. fruticosa performance. Cd2+ or Cu2+ enhanced malondialdehyde, suggesting reactive oxygen species-induced disruption of membrane integrity and oxidative stress in S. fruticosa. On the other hand, the activities of the antioxidant enzymes CAT, APX, and GPX diminished and mineral nutrition was disturbed by metal stress. S. fruticosa was able to synthesize PCs in response to TME toxicity. However, data indicate that GSH levels underwent a significant decrease in roots and leaves of S. fruticosa stressed by Cd2+ or Cu2+. The GSH depletion accompanied by the increase of phytochelatin concentration suggests the involvement of GSH in the synthesis of phytochelatins.